Research on scientific production in relation to the Silver Economy - Baños-Martínez, Vanesa; Limón Mendizabal, Mª Rosario (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The aim of this research, based on a literature review, is to raise awareness of a new reality associated with ageing, the silver economy, which has great potential not only because of the economic resources it is expected to mobilise but also because of the prominence and relevance given to older people as consumers of specialised products and services. The results give a clear picture of a scenario under construction, where European institutions seek to give visibility and impetus to this reality but society is not yet fully prepared to integrate this change.